2016
DOI: 10.1590/0102-33062015abb0267
|View full text |Cite
|
Sign up to set email alerts
|

Ecological significance of wood anatomy of Alseis pickelii Pilg. & Schmale (Rubiaceae) in a Tropical Dry Forest

Abstract: This work describes, analyzes and compares the wood anatomy of Alseis pickelii from two distinct sites in Tropical Dry Forest. One site is an exploited forest that was disturbed by deforestation whereas the other site is preserved and has not been logged since selective logging in the 1960's. For the evaluation of wood anatomy, plant material was processed following standard techniques for light microscopy and histochemical tests. The results indicated that A. pickelii did not vary qualitatively between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Only a few morphological differences displayed by S. coreana with S. tanakana, and S. sawafutagi include broadly obovate leaf lamina with coarsely serrate margin and bluish black fruit color instead of usually narrower, obovate to oblong leaf lamina with small and incurved toothed margin and bluish or black fruit (Ohwi, 1965;Chang et al, 2011;Kim and Kim, 2018). It has been suggested that some quantitative variations in the wood anatomical structures can be influenced by the growing conditions of the plant species (Baas, 1973;Carlquist, 2001;Campbell et al, 2016). Symplocos sawafutagi and S. tanaka which were collected form Pyeongchang-gun, Gangwon-do and Shinan-gun, Jeollanam-do, respectively, preferably grow deep in the forest with low sunlight whereas S. coreana which was collected form Miaksan, Seogwip-si, Jeju-do (in Korea this species only found in Jeju-do) usually prefer the edge of the forest with high sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few morphological differences displayed by S. coreana with S. tanakana, and S. sawafutagi include broadly obovate leaf lamina with coarsely serrate margin and bluish black fruit color instead of usually narrower, obovate to oblong leaf lamina with small and incurved toothed margin and bluish or black fruit (Ohwi, 1965;Chang et al, 2011;Kim and Kim, 2018). It has been suggested that some quantitative variations in the wood anatomical structures can be influenced by the growing conditions of the plant species (Baas, 1973;Carlquist, 2001;Campbell et al, 2016). Symplocos sawafutagi and S. tanaka which were collected form Pyeongchang-gun, Gangwon-do and Shinan-gun, Jeollanam-do, respectively, preferably grow deep in the forest with low sunlight whereas S. coreana which was collected form Miaksan, Seogwip-si, Jeju-do (in Korea this species only found in Jeju-do) usually prefer the edge of the forest with high sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…This general description of wood elements is typical to this study; however, they naturally differ in the quantitative dimensions of wood elements: vessel diameter range, vessel frequency, ray width, and ray height ranges. The variations of some wood characters of the studies may be anticipated to the ecological influences (Campbell et al, 2016).…”
Section: Diagrammentioning
confidence: 99%
“…Nonetheless, to our knowledge, there has been no study comparing vessel traits between representative species of logged and unlogged tree communities. Campbell et al (2016Campbell et al ( , 2018 analysed differences in vessel characteristics between logged and undisturbed forests in the Brazilian dry and wet tropics; however, both studies focused on a single tree species only. There is a gap of knowledge comparing wood anatomical traits between species of old-growth and selectively logged tree communities.…”
Section: © Forest Research Institute Malaysiamentioning
confidence: 99%